2006
DOI: 10.1088/0963-0252/15/4/036
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and frequency dependence of plasma currents in a 300 mm capacitively coupled plasma reactor

Abstract: There is much interest in scaling rf-excited capacitively coupled plasma reactors to larger sizes and to higher frequencies. As the size approaches operating wavelength, concerns arise about non-uniformity across the work piece, particularly in light of the well-documented slow-surface-wave phenomenon. We present measurements and calculations of spatial and frequency dependence of rf magnetic fields inside argon plasma in an industrially relevant, 300 mm plasma-processing chamber. The results show distinct dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 20 publications
2
49
1
Order By: Relevance
“…Another interesting feature of VHF CCP devices is the presence of higher harmonics of the applied frequency in the current and voltage characteristics of the discharges. Using a B-dot probe, Miller et al [22] detected the presence of higher harmonics in the electric field of the bulk plasma at a driving frequency of 60 and 176 MHz. Upadhyay et al [23] performed numerical simulations of electromagnetic wave phenomena in an asymmetric CCP excited at 60 MHz and showed the presence of higher harmonic content in the electric field up to the 20th harmonic of the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting feature of VHF CCP devices is the presence of higher harmonics of the applied frequency in the current and voltage characteristics of the discharges. Using a B-dot probe, Miller et al [22] detected the presence of higher harmonics in the electric field of the bulk plasma at a driving frequency of 60 and 176 MHz. Upadhyay et al [23] performed numerical simulations of electromagnetic wave phenomena in an asymmetric CCP excited at 60 MHz and showed the presence of higher harmonic content in the electric field up to the 20th harmonic of the excitation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The fields are calculated self-consistently with evolution of the electron plasma component using (13) to (15)). One can distinguish two different sets of boundary conditions depending on the way the discharge is driven, either with a voltage source or a current source.…”
Section: Nonlinear Model Problem With Moving Sheath Treated In Timmentioning
confidence: 99%
“…One can distinguish two different sets of boundary conditions depending on the way the discharge is driven, either with a voltage source or a current source. Whereas boundary conditions for (15) are same for both cases (see the discussion at the end of section III), the boundary conditions for (13) and (14) are different for each case.…”
Section: Nonlinear Model Problem With Moving Sheath Treated In Timmentioning
confidence: 99%
“…In recent years, several theoretical studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and experimental research [22][23][24][25][26][27][28][29][30] have been published on the plasma characteristics in a CCP sustained by VHF sources. Lieberman et al 6 first employed a uniform slab model to investigate the standing-wave and skin effects in VHF discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently they performed measurements in large area rectangular reactors, showing that a thin conducting layer present on the dielectric plate was sufficient to screen the electrode shape effect. 24 Miller et al 25,26 reported the magnetic field and other plasma parameters, for instance, line-integrated electron density and ion saturation current, as a function of frequency. Recently, Ahn and Chang 27 revealed, by means of a Langmuir probe and a B-dot probe, that the strong plasma inhomogeneity, detected in a cylindrical high frequency capacitive discharge at high pressures, was created by the significant inductive electric field near the radial edge.…”
Section: Introductionmentioning
confidence: 99%